A Facile Approach for the Mass Production of Submicro/Micro Poly (Lactic Acid) Fibrous Mats and Their Cytotoxicity Test towards Neural Stem Cells. - Hadjizadeh, Afra; Savoji, Houman; Ajji, Abdellah (BioMed Research International, 2016)
Despite many of the studies being conducted, the electrospinning of poly (lactic acid) (PLA), dissolved in its common solvents, is difficult to be continuously processed for mass production. This is due to the polymer solution droplet drying. Besides, the poor stretching capability of the polymer solution limits the production of small diameter fibers. To address these issues, we have examined the two following objectives: first, using an appropriate solvent system for the mass production of fibrous mats with fine-tunable fiber diameters; second, nontoxicity of the mats towards Neural Stem Cell (NSC). To this aim, TFA (trifluoroacetic acid) was used as a cosolvent, in a mixture with DCM (dichloromethane), and the solution viscosity, surface tension, electrical conductivity, and the continuity of the electrospinning process were compared with the solutions prepared with common single solvents. The binary solvent facilitated PLA electrospinning, resulting in a long lasting, stable electrospinning condition, due to the low surface tension and high conductivity of the binary-solvent system. The fiber diameter was tailored from nano to micro by varying effective parameters and examined by scanning electron microscopy (SEM) and image-processing software. Laminin-coated electrospun mats supported NSC expansion and spreading, as examined using AlamarBlue assay and fluorescent microscopy, respectively.